135La as an Auger-electron emitter for targeted internal radiotherapy. (29th December 2017) - Fonslet, J; Lee, B Q; Tran, T A; Siragusa, M; Jensen, M; Kibédi, T; Stuchbery, A E; Severin, G W
Abstract: 135 La has favorable nuclear and chemical properties for Auger-based targeted internal radiotherapy. Here we present detailed investigations of the production, emissions, and dosimetry related to 135 La therapy. 135 La was produced by 16.5 MeV proton irradiation of metallic nat Ba on a medical cyclotron, and was isolated and purified by trap-and-release on weak cation-exchange resin. The average production rate was 407 ± 19 MBq µ A −1 (saturation activity), and the radionuclidic purity was 98% at 20 h post irradiation. Chemical separation recovered > 98 % of the 135 La with an effective molar activity of 70 ± 20 GBq µ mol −1 . To better assess cellular and organ dosimetry of this nuclide, we have calculated the x-ray and Auger emission spectra using a Monte Carlo model accounting for effects of multiple vacancies during the Auger cascade. The generated Auger spectrum was used to calculate cellular S -factors. 135 La was produced with high specific activity, reactivity, radionuclidic purity, and yield. The emission spectrum and the dosimetry are favorable for internal radionuclide therapy.